Solid Versus Semi-solid Fermentation of Finger Millet (Eleusine coracana L.) - Karki, Dhan Bahadur; Kharel, Ganga Prasad (Journal of Food Science and Technology Nepal, 2013)
Effects of solid versus semi-solid fermentations on the chemical and organoleptic qualities of finger millet Jand were studied. Millet was fermented under solid and semi-solid states by using defined fermentation starter and the Jand was subjected to chemical and sensory analyses. Results indicated that except on moisture and alcohol contents, semi-solid fermentation reflected a significant effect (p<0.05) on the chemical characteristics of millet Jand. TSS, acidity and ester contents increased substantially in semi-solid fermentation as compared to solid-state one. Millet fermented with 50% water addition had more than 2-folds higher total acidity than that of solid-state fermented and every 50% increase in water addition nearly doubled the fixed acidity of the products. No remarkable improvement on the chemical and sensory quality of millet Jand was found by using semi-solid state fermentation. J. Food Sci. Technol. Nepal, Vol. 6 (31-35), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8257